Unusual Presentation of Popliteal Cyst on Magnetic Resonance Imaging - Tsuyoshi Ohishi; Masaaki Takahashi; Daisuke Suzuki; Yukihiro Matsuyama (Case Reports in Orthopedics)
Popliteal cyst commonly presents as an ellipsoid mass with uniform low signal intensity on T1-weighted magnetic resonance images and high signal intensity on T2-weighted images. Here, we describe a popliteal cyst with unusual appearance on magnetic resonance imaging, including heterogeneous intermediate signal intensity on T2-weighted images. Arthroscopic cyst decompression revealed that the cyst was filled with necrotic synovial villi, indicative of rheumatoid arthritis. Arthroscopic enlargement of unidirectional valvular slits with synovectomy was useful for the final diagnosis and treatment.